1977
DOI: 10.1007/bf01078348
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal intramural pseudodiverticulosis

Abstract: Three cases of esophageal intramural pseudodiverticulosis (EIP) are described and the literature reviewed. We conclude that EIP is an inflammatory disease of unknown etiology characterized by dilatation of the esophageal submucosal glandular elements. The classic radiographic picture which is that of collar-button-shaped outpouchings projecting in a perpendicular fashion from the luminal surface is mainly related to dilatation in the glandular ductal system. It is usually diagnosed in the sixth and seventh dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
4

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
0
23
0
4
Order By: Relevance
“…Others have proposed that the presence of submucosal glands in excessive numbers results in recurrent or chronic inflammation and cystic dilatation with hyper plastic and metaplastic changes occurring within the cyst walls [2]. Some autopsy studies, however, have corrobo rated the proposition that the pseudodiverticulae repre sent dilatations of excretory ducts of the normal submu cosal glands of the esophagus [3][4][5]. In these studies, the submucosal glands did not participate in the formation of the pseudodiverticulae and they were not increased in number.…”
Section: Discussionmentioning
confidence: 90%
“…Others have proposed that the presence of submucosal glands in excessive numbers results in recurrent or chronic inflammation and cystic dilatation with hyper plastic and metaplastic changes occurring within the cyst walls [2]. Some autopsy studies, however, have corrobo rated the proposition that the pseudodiverticulae repre sent dilatations of excretory ducts of the normal submu cosal glands of the esophagus [3][4][5]. In these studies, the submucosal glands did not participate in the formation of the pseudodiverticulae and they were not increased in number.…”
Section: Discussionmentioning
confidence: 90%
“…Histologically, pathologically dilated submucosal glands and excretory ducts were detected. [4][5][6][7] Considering the presence of inflammatory cells around excretory ducts, it has been suggested that the ducts were obstructed by inflammation of epithelial cells or mucus around the ducts. 4,5 On the contrary, others asserted submucosal fibrosis caused by chronic irritation had resulted in the obstruction of the ductal orifices.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested the conditions predispos ing to EIPD development and the condition itself may be more common than previously thought. There appears to be a slight male pre dominance (male:female ratio 1.4:1) [4,5]; the age ranges from 1 to 86 years, 56% of the patients being in their 7th and 8th decades of life. There may be a predominance among …”
Section: Discussionmentioning
confidence: 99%
“…Motility studies are usually done in the context of the dysphagia evalua tion. Disturbances have been noted in ap proximately 77% of the patients [4], There is no characteristic pattern of motility as the entire spectrum from aperistalsis to prolonged high-amplitude contractions has been de scribed [4,9]. As many patients have diabetes mellitus, an autonomic neuropathy is postu lated.…”
Section: Pathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation